“Por uma história que atinja a maior parte da população”: a produção didática do projeto resgate da história local dos municípios paraibanos - Araújo, Jéssica Hellen dos Santos (2022)
This work aims to analyze a collection of the Didactic Materials Series developed in the 1990s by the Projeto Resgate do Processo Histórico e Cultural dos Municípios Paraibanos. We examined the research carried out in full in six municipalities in Paraíba – Patos, Ingá, Pedras de Fogo, Conde, Cabedelo and Areia – with the objective of analyzing the history of the Project’s conception and performance, the construction of the manuals and the methodology used by the group of research. We insert the case of Serra Branca, which even with the data collection and investigations already carried out from 2007 onwards, has not yet been embodied in a book. The sources used were teaching materials and interviews given by the team of teachers, coordinators and research fellows at the time, and a copy of the project in its original format. This work will be built from the theoretical perspectives of Social History, seeking to specify the outline of Local History, seen as a methodological resource that offers the possibility of situating the significant problems of the history of the present time, insofar as it seeks to analyze the formation of spaces social and community articulation.